Digital Marketing Strategy To Increase Sales At The Hawwapassion Store, Bengkulu City - Andini, Puja; Susanti , Neri; Astuti, Kamelia (Universitas Dehasen Bengkulu, 2024)
This research aims to analyze the digital marketing strategy implemented by the Hawwa Passion Store in Bengkulu City in an effort to increase sales. Through participatory methods and focus group discussions, this research evaluates the effectiveness of the use of social media and e-commerce platforms and identifies the challenges faced by business actors.The research results show that implementing digital marketing strategies, especially through social media such as Instagram and Facebook as well as e-commerce platforms such as Tokopedia and Shopee, has succeeded in increasing sales of the Hawwa Passion Shop by 40%. The use of engaging visual content and digital advertising campaigns play an important role in capturing consumer attention and increasing engagement.However, this research also found several limitations, including limited technical knowledge in content management and relatively high digital advertising costs. Apart from that, unstable internet access in several areas of Bengkulu City is also an obstacle in implementing this strategy.The main contribution of this research is to provide insight into effective digital marketing practices for small and medium enterprises in the thrifting sector. It is hoped that the resulting recommendations can help business actors optimize their digital marketing strategies, overcome existing obstacles, and ultimately increase sales and business growth.